Event Organizer's Responsibility for Royalty Payments to Songwriters in Music Concerts - Oktavianto Setyo Nugroho; Setyawati, Setyawati (SEAN Institute, 2025)
Music concerts as a form of public performance often use copyrighted works in the form of songs produced by creators. Law Number 28 of 2014 concerning Copyright and Government Regulation Number 56 of 2021 have explicitly regulated the obligation of every party that uses songs or music for commercial purposes to pay royalties to creators, copyright holders, and neighboring rights owners. Event organizers are responsible for ensuring that every song used in a concert has obtained permission from the creator or rights holder through a royalty payment mechanism. However, in practice, many event organizers still ignore this obligation, resulting in violations of the economic rights of songwriters. This study uses a normative juridical method with a legislative and literature study approach, as well as secondary data for analysis. The results of the study show that although Law Number 28 of 2014, Government Regulation Number 56 of 2021, Decree of the Minister of Law and Human Rights of the Republic of Indonesia Number: HKI.2.OT.03.01.02 of 2016, and LMKN Decree Number: 20150512KM/LMKN -Pleno/Tarif Royalti/2016 clearly regulate the payment of royalties to songwriters, their implementation has not been maximally effective. Lack of legal awareness, production cost considerations, minimal supervision and law enforcement, the assumption that royalties are already included in artists' payments, and administrative processes that are considered difficult pose challenges to royalty payments. Therefore, it is necessary to strengthen law enforcement, increase awareness, and promote collaboration between the government, LMKN, and entertainment industry players so that royalty payments can run smoothly